The Analysis of Vocabulary Usage in The Online Game Application ”Mobile Legend’’ at Junior High School - Mifta Farid; Muh. Tahir; Iskandar; Muhammad Arham; Agus Salim Jirong (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study explores the analysis of vocabulary usage in the online game application Mobile Legends at Junior High School. Using a qualitative design, the study involved 10 ninth-grade students as participants, selected for their active engagement with the game. Data were collected through observation, semi-structured interviews, and documentation. The findings reveal that students frequently acquired vocabulary related to gameplay, such as cooldown (CD), buff, nerf, ulti, and backdoor. These terms were retained because they were repeatedly used and directly connected to in-game actions. Students reported that the interactive features of Mobile Legends, including quick chat, voice chat, and subtitles, facilitated vocabulary learning in an authentic context. The results indicate that Mobile Legends can serve as a supplementary medium for vocabulary acquisition among Generation Z learners. However, potential negative impacts, such as exposure to offensive language and excessive play, must also be considered. The study suggests that game-based learning should be integrated strategically into EFL classrooms to maximize benefits while minimizing risks.